Perceived Employability, Academic Commitment, and Competency of University Students During the COVID-19 Pandemic: An Exploratory Study of Student Well-Being - Capone, Vincenza; Marino, Leda; Park, Miriam Sang-Ah (Frontiers in Psychology, 2021)
Coronavirus disease 2019 (COVID-19) outbreak has led to the closure of schools and universities, which forced students to reorganize their daily and academic lives. The pandemic has thus impacted the well-being of students in various ways. This study aimed to investigate the relationship between the perceived employability, self-efficacy, ambition, organizational commitment, and career planning of students, as well as mental well-being, student engagement, and academic burnout during the pandemic. A total of 269 Italian university students participated in an online questionnaire. Our results highlight that students experienced high levels of uncertainty about their employability and career planning. In contrast, however, they reported healthy levels of mental well-being and student engagement, high career ambitions, and strong self-efficacy, despite the impact of COVID-19. We suggested that intervention and supportive programs should be offered to students over the long term in order to minimize the negative impact of the pandemic.